Serial Murder, Serial Consummerism: Bret Easton Ellis’s American Psycho (1991) - Baelo Allué, Sonia (Miscelánea: A Journal of English and American Studies, 2002)
Bret Easton Ellis is a representative blank fiction writer whose novels deal with violence, indulgence, sexual excess, decadence, consumerism and commerce. In American Psycho (1991) he focuses on the phenomenon of the serial killer. The aim of this paper is to look into the ways in which the seriality of the serial killer’s murders is linked to the seriality provided by different forms of mass culture: talk shows, daily news, advertisements, pop music, magazines and consumerism in general. Our society’s never-ending serial consumerism is mirrored by the serial killer’s never-ending killings. Taken to its ultimate consequences, consumerism includes everything, which dehumanises people and blurs the difference between consuming objects and consuming human beings. The concept of seriality is deeply embedded in our culture, and is shared by serial killer fiction, mass cultural productions, and by consumerism, which may account for the current popularity of the serial killer.
Keywords: Bret Easton Ellis; American Psycho; blank fiction; consumerism; serial killers